A Review on Polymeric Nano Micelles Based Delivery to the Posterior Segment of the Eye - Devi, Sheetal; Bhatt, Shailendra; Saini, Vipin; Kumar, Manish; Deep, Aman (Nanoscience & Nanotechnology-Asia, 2020)
Introduction: Many nanoformulations have been designed and evaluated for ocular drug delivery system consistently. These nanoformulations are designed for prolonged retention and course time, stable, efficient and reversible drug loading. The ocular bioavailability is very less when the drug is given through topically. Various anatomical and physiological limitations, for example, tear turnover, nasal lachrymal waste, reflex squinting, and visual static and dynamic hindrances cause the challenges and delay the ocular drug permeation because of the limitation that less than 5% dose can reach into the ocular tissues. Different types of Polymeric micelles were prepared to overcome the above challenges. Polymeric nano micelles are prepared by different methods, such as direct dissolution, dialysis method, Oil-in-water emulsion, solvent evaporation, co-solvent evaporation, and freeze-drying method.
Keywords: tear turnover